EPIDEMIOLOGICAL CHARACTERISTICS OF GIARDIASIS IN THE AREA OF BELGRADE DURING THE PERIOD FROM 2007 TO 2020 - Giljača, Sonja (Acta medicae Medianae, 2023)
The aim of this paper was to analyze the epidemiological characteristics of Giardiasis around Belgrade from 2007 to 2020. A descriptive epidemiological study was applied. In the observed period, 265 new cases of giardiasis were registered in Belgrade, the average raw incidence was 18.92/100,000. Men (56%) were more likely to develop giardiasis than women (44%). Highest age-specific incidence rate was at the age of 2 years (10.3/100,000). The largest number of patients was registered in municipality Savski venac 106 (40%). Seasonal distribution indicates that the largest number of patients was registered in September and October. The epidemiological situation in Belgrade in the observed period shows a declining tendency of the number of patients and the incidence rate, which is most likely the result of improved hygienic and sanitary living conditions.
Keywords: giardiasis, protozoa, diarrhea, hygiene